2007
DOI: 10.1677/erc-06-0054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a phytoestrogen-containing soy extract on the growth-inhibitory activity of ICI 182 780 in an experimental model of estrogen-dependent breast cancer

Abstract: The study reported here was designed to determine whether a phytoestrogen-containing soy extract (SSE) could negate/overwhelm the inhibitory effects of ICI 182 780 on the growth of estrogen-sustained human breast cancer xenografts (MCF-7), in ovariectomized athymic mice. As expected, estradiol-supplemented tumors did not grow over the study period in ICI 182 780-treated females; concomitant administration of 50 mg/kg per day SSE slightly potentiated the inhibitory activity of the drug, while at 100 mg/kg per d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Finally, results obtained in this study did not show any modulation of IGF-I serum levels upon administration of SSE, a finding in keeping with previous results by our and other groups in preclinical models of estrogen-dependent breast cancer (28,29) but inconsistent with other literature data showing a reduction in circulating levels of this growth factor in mice bearing human prostate or bladder tumors following consumption of dietary soy products (30,31). The reason why effects of soy isoflavones on IGF-I signaling are seen in some experimental systems but not in others is not understood, possibly involving differences in both cell lines and/or experimental conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, results obtained in this study did not show any modulation of IGF-I serum levels upon administration of SSE, a finding in keeping with previous results by our and other groups in preclinical models of estrogen-dependent breast cancer (28,29) but inconsistent with other literature data showing a reduction in circulating levels of this growth factor in mice bearing human prostate or bladder tumors following consumption of dietary soy products (30,31). The reason why effects of soy isoflavones on IGF-I signaling are seen in some experimental systems but not in others is not understood, possibly involving differences in both cell lines and/or experimental conditions.…”
Section: Discussionsupporting
confidence: 93%
“…A soybean purified extract containing isoflavones glycosides genistein and daidzein (14.7%; Soyselect ® ), was kindly donated by Indena (Milan, Italy). Soyselect ® is a standardized extract obtained from soy with a double standardization procedure and which contains 13%–17% of isoflavone glycosides genistein and daidzein and <18% of B-group saponins, as quantified by HPLC [ 34 , 35 ]. The product is prepared by extracting ripe whole soy beans or oil-free soy flour with aliphatic alcohols through an industrial manufacturing proprietary process [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Gallo et al [53] studied the effect of soy extract, standardized on the content of genistein and daidzein, on the action of fulvestrant, which inhibited the formation of breast cancer in ovariectomized mice. Low doses of phytoestrogens -50 mg soy extract/kg bw/day, have been shown to slightly increase the inhibitory effect of fulvestrant, while higher doses -100 mg soy extract/kg bw/day significantly reduced the antitumour activity of the drug [53].…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%
“…Gallo et al [53] studied the effect of soy extract, standardized on the content of genistein and daidzein, on the action of fulvestrant, which inhibited the formation of breast cancer in ovariectomized mice. Low doses of phytoestrogens -50 mg soy extract/kg bw/day, have been shown to slightly increase the inhibitory effect of fulvestrant, while higher doses -100 mg soy extract/kg bw/day significantly reduced the antitumour activity of the drug [53]. In contrast, the lack of interaction between fulvestrant and genistein was indicated by the results of experiments by Dess et al [54], who showed that low doses of genistein (1µM) and zearalenone (1nM), similar to the pesticide DDT (dichlorodiphenyltrichloroethane known for breast cancer proliferation promoting properties), increase the activity of cyclin-dependent kinase 2 (Cdk2), synthesis of cyclin D1 and hyperphosphorylation of pRbl05 (retinoblastoma protein) in MCF-7 cells.…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%